Partitioning of Mg, Sr, Ba and U into a subaqueous calcite speleothem. (1st November 2019) - Drysdale, Russell N.; Zanchetta, Giovanni; Baneschi, Ilaria; Guidi, Massimo; Isola, Ilaria; Couchoud, Isabelle; Piccini, Leonardo; Greig, Alan; Wong, Henri; Woodhead, Jon D.; Regattieri, Eleonora; Corrick, Ellen; et al.
Abstract: The trace-element geochemistry of speleothems is becoming increasingly used for reconstructing palaeoclimate, with a particular emphasis on elements whose concentrations vary according to hydrological conditions at the cave site (e.g. Mg, Sr, Ba and U). An important step in interpreting trace-element abundances is understanding the underlying processes of their incorporation. This includes quantifying the fractionation between the solution and speleothem carbonate via partition coefficients (where the partitioning ( D ) of element X ( D X ) is the molar ratio [X/Ca] in the calcite divided by the molar ratio [X/Ca] in the parent water) and evaluating the degree of spatial variability across time-constant speleothem layers. Previous studies of how these elements are incorporated into speleothems have focused primarily on stalagmites and their source waters in natural cave settings, or have used synthetic solutions under cave-analogue laboratory conditions to produce similar dripstones. However, dripstones are not the only speleothem types capable of yielding useful palaeoclimate information. In this study, we investigate the incorporation of Mg, Sr, Ba and U into a subaqueous calcite speleothem (CD3) growing in a natural cave pool in Italy. Pool-water measurements extending back 15 years reveal a remarkably stable geochemical environment owing to the deep cave setting, enabling the calculation of precise solution [X/Ca]. We determine the trace element variability of 'modern' subaqueous calcite from a drill core taken through CD3 to derive D Mg, D Sr, D Ba and D U then compare these with published cave, cave-analogue and seawater-analogue studies. The D Mg for CD3 is anomalously high (0.042 ± 0.002) compared to previous estimates at similar temperatures (∼8 °C). The D Sr (0.100 ± 0.007) is similar to previously reported values, but data from this study as well as those from Tremaine and Froelich (2013) and Day and Henderson (2013) suggest that [Na/Sr] might play an important role in Sr incorporation through the potential for Na to outcompete Sr for calcite non-lattice sites. D Ba in CD3 (0.086 ± 0.008) is similar to values derived by Day and Henderson (2013) under cave-analogue conditions, whilst D U (0.013 ± 0.002) is almost an order of magnitude lower, possibly due to the unusually slow speleothem growth rates (<1 μm a −1 ), which could expose the crystal surfaces to leaching of uranyl carbonate. Finally, laser-ablation ICP-MS analysis of the upper 7 μm of CD3, regarded as 'modern' for the purposes of this study, reveals considerable heterogeneity, particularly for Sr, Ba and U, which is potentially indicative of compositional zoning. This reinforces the need to conduct 2D mapping and/or multiple laser passes to capture the range of time-equivalent elemental variations prior to palaeoclimate interpretation.